Ormeloxifene-induced unfolded protein response contributes to autophagy-associated apoptosis via disruption of Akt/mTOR and activation of JNK - Arindam Bhattacharjee (Nature Portfolio, 2018)
Abstract Autophagy, a regulated nutrient recycling program can affect both cell survival and cell death. Here, we show that Ormeloxifene (ORM), a selective estrogen receptor modulator approved for oral contraceptive use induces autophagic flux in ovarian cancer cells, which is activated by an ER stress response upstream of autophagy. The ER stress response is characterized by activation of IRE1α, PERK and ATF6 and is under regulation of JNK. Pharmacological inhibition of either autophagy or ER stress increased cell survival, as did silencing of autophagy proteins LC3 and Beclin 1, implying that ORM-induced autophagy is pro-death in nature. Ultrastructural observations of treated cells confirmed stages of autophagic maturation. Caspase-dependent apoptosis succeeded these events and was characterized by generation of reactive oxygen species and disruption of mitochondrial membrane potential. A concomitant inhibition of the Akt/mTOR axis was also observed with possible regulation of Akt by ORM. ORM inhibited tumor growth in ovarian xenograft model and displayed autophagic activity. In summary, in vitro and in vivo results reveal that ORM induces autophagy-associated cell death to attenuate proliferation of ovarian cancer cells. Our results demonstrate that using ORM in combination with ER stress and autophagy modulators could offer better therapeutic outcome in ovarian cancer.